2020
DOI: 10.3390/jof6040335
|View full text |Cite
|
Sign up to set email alerts
|

Rye Snow Mold-Associated Microdochium nivale Strains Inhabiting a Common Area: Variability in Genetics, Morphotype, Extracellular Enzymatic Activities, and Virulence

Abstract: Snow mold is a severe plant disease caused by psychrophilic or psychrotolerant fungi, of which Microdochium species are the most harmful. A clear understanding of Microdochium biology has many gaps; the pathocomplex and its dynamic are poorly characterized, virulence factors are unknown, genome sequences are not available, and the criteria of plant snow mold resistance are not elucidated. Our study aimed to identify comprehensive characteristics of a local community of snow mold-causing Microdochium species co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 163 publications
0
16
0
2
Order By: Relevance
“…This is due to the fact that a small amount of breeding material with increased SM resistance is used in contemporary breeding. We searched the SM resistance sources in the Tatarstan Republic, where a fairly high level of SM is a typical situation [ 46 ], for two years in which the level of natural development of the disease was different: in 2021, the level of SM was significantly higher than in 2020. The variation in SM severity during two years of observation was likely related to different durations of snow cover—102 and 150 days in 2020 and 2021, respectively ( Table 6 )—which is consistent with the confinement of SM outbreaks to prolonged periods of snow cover [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the fact that a small amount of breeding material with increased SM resistance is used in contemporary breeding. We searched the SM resistance sources in the Tatarstan Republic, where a fairly high level of SM is a typical situation [ 46 ], for two years in which the level of natural development of the disease was different: in 2021, the level of SM was significantly higher than in 2020. The variation in SM severity during two years of observation was likely related to different durations of snow cover—102 and 150 days in 2020 and 2021, respectively ( Table 6 )—which is consistent with the confinement of SM outbreaks to prolonged periods of snow cover [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Samuels & I.C. Hallett strain F00628 from the collection of KSC [ 46 ]. In 2019, the inoculum was prepared as follows: M. nivale was grown in potato-sucrose medium for 20 days in darkness at 20 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Although plants bring beneficial microorganisms, such as PGPR and diseasesuppressing microorganisms, it has been evident that they can also bring phytopathogens as well as human pathogenic bacteria. These harmful bacteria may enter the food chain, can cause plant disease, and can alter the entire microbiome composition (Gorshkov et al, 2020). Therefore, tools such as metagenomics, for example, offer a promising strategy to diagnose these phytopathogens (Chiu and Miller, 2019).…”
Section: Omics Approaches To Unveil Plant-associated Microbiotamentioning
confidence: 99%
“…Although the selection mechanisms used by plants significantly enrich the plant microbiome with beneficial microorganisms, such as plant growth-promoting rhizobacteria (PGPR) [ 76 ] and disease suppressing microorganisms [ 76 , 82 , 83 ], many researchers have shown that the rhizosphere and all plant compartments often contain both phytopathogens and human pathogenic bacteria as well as producers of toxins that can enter the food chain directly from plants [ 84 , 85 , 86 ]. Moreover, if a plant disease occurs, it not only promotes the multiplication of the pathogen, but is also accompanied by dramatic changes in the entire microbiome [ 87 ]. In this regard, metagenomics is a promising tool for phytopathogen diagnosis, and food quality control, as well as developing clinical metagenomics [ 88 ].…”
Section: Genomicsmentioning
confidence: 99%